Issues of Inclusion and Special Education in the Creative Heritage of Sofia Rusova - Dzhus, Oksana (Journal of Vasyl Stefanyk Precarpathian National University, 2020)
The article analyzes the issues of inclusion and special education in the creative heritage of Sofia Rusova – teacher, citizen, politician, state maker, who considered them in the context of world scientific achievements of the interwar period of the XX century. Inclusion, as a process of increasing the participation of all citizens in society, including those with physical or mental disabilities, involves the development and implementation of specific solutions that will allow each person to participate equally in academic and public life. The evolution of the idea of inclusion and the birth of special education S. Rusova closely linked with the understanding and interpretation of the leading principles of pedagogy, general and social psychology, sociology, philosophy of education, historical and pedagogical searches of the late XIX - early XX century. Perhaps the most important source of new pedagogical ideas of S. Rusova, embodied in the writings of the interwar period (“New School of Social Education”, “Education and Sociology of Durkheim”, “Social Education: Its Importance in Public Life”, “Public Issues of Education” became acquainted with the latest trends in Western European pedagogy, which allowed her to keep up with the times, psychologize pedagogy. Extensive education, fluency in the leading European languages (first and foremost, French) made it possible for S. Rusova to access the original literature - works by J. Dewey, E. Claapared, G. Kerschensteiner, V. Lai, E. Meiman, and G. Spencer with the most prominent pedagogical figures of the 1920s and 1930s, including O. Decroly and M. Montessori, and studying the experience of their practical work. Guided by the statement that “ development of the child is influenced by three main factors: education, heritage, and environment”, based on the experiments of foreign (German, Belgian, Czech) researches, the scientist revealed the specifics of social and educational impact of the environment, preparing the groundwork inclusion as a set of conditions, methods and means of their implementation for joint learning, education and development of the educational recipients, taking into account their needsand opportunities. At the same time, I emphasize the shaft that no child “is passively influenced by the environment: it takes from it what its individuality seeks.” The issue of special education, in particular, the psychological and pedagogical principles of working with children with intellectual disabilities, is most fully revealed in S. Rusova's work, “Something about defective children in school”. It clearly traces the idea that children of all walks of life are necessarily subject to process education and training. According to S. Rusova, children with deviant behavior (in particular, “child offenders”), for whom the conditions for education as a factor of their re-education should be created, and for the needs of such schools, should not be left out of the educational influence in order to organize teacher training “with a deep psychological understanding of their sick students, with a heart warmed with love for them, and with a certain understanding of their social and pedagogical task: to return these children to citizenship ...”. Summarizing the above, it can be argued that the issues of inclusion, studying, education of children and young people with special educational needs, as represented by the property of Sofia Rusova are a significant contribution to Ukrainian and world pedagogical thought, an important factor in the revival of national educational systems in the teaching experiences of the past.